Participation as “attingere” and Saint Thomas’ commentary on John 6:57 - Johannes von Voorst (Polonia Sacra)
Saint Thomas Aquinas’ notion of participation is developed by Cornelio Fabro with the notion of ‘attingere’. In this essay I address the importance of ‘participare’ as attingere by uncovering it in Aquinas’ commentary on John 6:57. I introduce the notion of supernatural participation of grace and Fabro’s development of the notions of ‘attingere’ as ‘partecipare per similitudinem’ and ‘partecipare per operationem’ for a fuller understanding of the notion of participation that Fabro holds to be so essential. Afterwards we will see a concrete example in the uncovering of said notions in the Angelic Doctor’s commentary on a central verse of the Bread of Life discourse. Thus, we will be able to see both (a) the importance of the notion of ‘participare’ and ‘attingere’ in Saint Thomas’ work, and (b) have a more profound understanding of a key aspect of the thought of the Doctor Communis on grace and the Eucharist.